Monitoring Oxford-AstraZeneca COVID-19 vaccine Side Effects in Faridpur, Bangladesh: A Prospective Study - Arif, Khan Md; Biswas, Rajib; Islam, M M Shahin Ul; Rahman, ATM Ataur (Bangabandhu Sheikh Mujib Medical College Journal, 2024)
The Oxford-AstraZeneca COVID-19 vaccine is effective in preventing illness and death from COVID-19. In this study, we aimed to evaluate the safety of the Oxford-AstraZeneca COVID-19 vaccine in a population in Faridpur, Bangladesh. The study population included individuals who received both doses of the vaccine from Bangabandhu Sheikh Mujib Medical College Hospital in Faridpur. We followed up with these individuals via phone interviews one week and one month after each vaccination to gather information about side effects. We found that the overall incidence of systemic and injection site side effects after the first and second doses was 36.5% and 34.7%, and 68.2% and 61.3%, respectively, among the 2256 studies population. The most common systemic side effects were fatigue, fever, and muscle pain, while the most common injection site symptoms were tenderness, pain, and redness. These side effects generally resolve within 24-72 hours after vaccination. Only a small percentage of individuals (1.3% after the first dose and 0.5% after the second dose) sought medical attention for their side effects. We also found that individuals with a history of chronic disease and those who had a history of COVID-19 symptoms had a significantly higher likelihood of experiencing side effects. In conclusion, the Oxford-AstraZeneca COVID-19 vaccine was generally safe in this population, with a low incidence of side effects requiring medical attention. Bangabandhu Sheikh Mujib Med. Coll. J. 2024;3(1):16-21